Dampak Pengembangan Pariwisata terhadap Budaya Masyarakat Lokal (Studi Kasus Desa Wisata Fatumnasi, Kabupaten Timor Tengah Selatan, Provinsi Nusa Tenggara Timur) - Eky, Feny Susana; Meko, Pasafikus Mala; Mantolas, Maria Christina; Eky, Elsa Febrista (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2025)
The purpose of this study was to determine the impact of tourism development on local culture, with a case study of Fatumnasi Tourism Village in South Central Timor Regency, East Nusa Tenggara Province. The type of research used is descriptive qualitative. Data collection techniques include observation, interviews, and documentation. In-depth and structured interviews were conducted with 10 informants, including village heads, traditional leaders, community leaders, and members of tourism awareness groups (pokdarwis). The data obtained were analyzed through the stages of data reduction, data presentation, drawing conclusions and verification, and final conclusions. The results of the study showed that tourism development had no impact on 12 cultural elements that were cultural attractions, namely: language, community customs, handicrafts, food and eating habits, music and art, historical sites, work methods and technology, beliefs (religion), architectural forms and characteristics, dress codes, education systems, and leisure activities. However, tourism development in Fatumnasi Tourism Village has an impact on shifting cultural values. Even though there has been a shift in cultural values, the cultural roots of the Fatumnasi community remain firmly embedded in their thinking and character, as seen in their daily lives. Another finding shows that increased tourist visits encourage them to continue preserving their culture. Keywords: impact of tourism development, local culture